2013
DOI: 10.1111/nph.12497
|View full text |Cite
|
Sign up to set email alerts
|

Combined NanoSIMS and synchrotron X‐ray fluorescence reveal distinct cellular and subcellular distribution patterns of trace elements in rice tissues

Abstract: SummaryThe cellular and subcellular distributions of trace elements can provide important clues to understanding how the elements are transported and stored in plant cells, but mapping their distributions is a challenging task.The distributions of arsenic, iron, zinc, manganese and copper, as well as physiologically related macro-elements, were mapped in the node, internode and leaf sheath of rice (Oryza sativa) using synchrotron X-ray fluorescence (S-XRF) and high-resolution secondary ion mass spectrometry (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
143
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(152 citation statements)
references
References 41 publications
4
143
1
4
Order By: Relevance
“…Kopittke et al [20] demonstrated that As(III) i is quickly complexed with glutathione (GSH) in rice roots exposed to As(III) i in hydroponic media. Using NanoSIMS, Moore and colleagues provided evidence for As co-localization with S in vacuoles within the pericycle for rice exposed to As(III) i [36,37]. Although µXRF does not provide as fine a resolution as NanoSIMS, our data partially corroborate this past work as we also observed co-localization of As(III) with S in the more mature root portion 500 µm from the apex within or near the vascular bundle ( Figure 4).…”
Section: Discussionsupporting
confidence: 82%
“…Kopittke et al [20] demonstrated that As(III) i is quickly complexed with glutathione (GSH) in rice roots exposed to As(III) i in hydroponic media. Using NanoSIMS, Moore and colleagues provided evidence for As co-localization with S in vacuoles within the pericycle for rice exposed to As(III) i [36,37]. Although µXRF does not provide as fine a resolution as NanoSIMS, our data partially corroborate this past work as we also observed co-localization of As(III) with S in the more mature root portion 500 µm from the apex within or near the vascular bundle ( Figure 4).…”
Section: Discussionsupporting
confidence: 82%
“…The formation of insoluble Fe-P complexes in the vacuoles explains the relatively low mobility of Fe in plants (Marschner 2012). Copper shows a very different distribution pattern from that of the other transition metals with a strong localization to various types of vascular bundles mainly in the cell walls (Moore et al 2014). A similar study about roots will contribute to explain the Si role on metal accumulation at non-toxic concentrations and the possibilities of the accumulated metal to be transported to the shoot or not.…”
Section: Perspectivesmentioning
confidence: 99%
“…Silicon generally showed cell wall localization and no Si is detected in the vacuoles, probably because of the lack of Si transporters located in the tonoplast (Moore et al 2014). Moreover, Si was found to accumulate in oval granules, likely to be the starch grains, in the cytoplasm of the fundamental parenchyma of the internode (Moore et al 2014). Within the node, Zn was localized in the vacuoles of the parenchyma cell bridge bordering the enlarged and diffused vascular bundles, whereas Fe and Mn were localized in the fundamental parenchyma cells, with Fe being strongly co-localized with phosphorus in the vacuoles.…”
Section: Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations